2015
DOI: 10.1186/s12934-015-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

L-lactic acid production by Aspergillus brasiliensis overexpressing the heterologous ldha gene from Rhizopus oryzae

Abstract: BackgroundLactic acid is the building block of poly-lactic acid (PLA), a biopolymer that could be set to replace petroleum-based plastics. To make lactic acid production cost-effective, the production process should be carried out at low pH, in low-nutrient media, and with a low-cost carbon source. Yeasts have been engineered to produce high levels of lactic acid at low pH from glucose but not from carbohydrate polymers (e.g. cellulose, hemicellulose, starch). Aspergilli are versatile microbial cell factories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
(60 reference statements)
0
23
0
Order By: Relevance
“…Starch was highest in HQCF (65.17%) and lowest in yellow kpokpo gari (53.60%). The low starch content in the Southern Guinea savannah products could be attributed to the starch content of varieties of cassava preferred in the zone and the activities of microorganisms, which might have converted the starch into organic acids (Liaud et al, 2015), resulting in the low starch content. This observation agrees with that of Ray and Sivakumar (2009).…”
Section: Please Cite This Article As 'In Press' Quality Assurance Andmentioning
confidence: 99%
“…Starch was highest in HQCF (65.17%) and lowest in yellow kpokpo gari (53.60%). The low starch content in the Southern Guinea savannah products could be attributed to the starch content of varieties of cassava preferred in the zone and the activities of microorganisms, which might have converted the starch into organic acids (Liaud et al, 2015), resulting in the low starch content. This observation agrees with that of Ray and Sivakumar (2009).…”
Section: Please Cite This Article As 'In Press' Quality Assurance Andmentioning
confidence: 99%
“…For example, there has been an increasing demand of lactic acid in the manufacturing of biodegradable polylactic acid materials used as an alternative to petroleum-derived plastics [3]. It was estimated that the worldwide demand for lactic acid would reach 1,000,000 metric tons by the year 2020 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, engineered microbial strains have been reported for the efficacious production of lactic acid. Liaud et al [4] indicated that Aspergillus brasiliensis could produce more lactic acid as a result of the insertion of recombinant idhA genes obtained from R. oryzae. Metabolically engineered Saccharomyces cerevisiae and A. oryzae could produce lactic acid more efficiently if a bovine L-lactate dehydrogenase gene (LDH) was integrated into their genome [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, gypsum is not produced. Liaud et al (2015) obtained the first Aspergillus strains able to produce large amounts of LA by inserting recombinant ldhA genes from R. oryzae into a wild-type A. brasiliensis strain. The strain produced 32.2 g/L of LA, with a yield of 0.44 g/g from glucose in fed-batch fermentation with a final pH of 3.2 (Abdel-Rahman and Sonomoto 2016).…”
Section: Eli 1969mentioning
confidence: 99%
“…The strain produced 32.2 g/L of LA, with a yield of 0.44 g/g from glucose in fed-batch fermentation with a final pH of 3.2 (Abdel-Rahman and Sonomoto 2016). The advantages of these strains are they can grow at low pH and utilize cheap abundant carbon sources such as plant biomass (Liaud et al 2015). Another option to overcome the pH inhibition is the in situ removal of LA to prevent microorganism inhibition using conventional electrodialysis, solvent extraction, adsorption, and membrane bioreactors (Abdel-Rahman and Sonomoto 2016).…”
Section: Eli 1969mentioning
confidence: 99%